Peptide-Conjugated Nano Delivery Systems for Therapy and Diagnosis of Cancer - Isha Gaurav; Xuehan Wang; Abhimanyu Thakur; Ashok Iyaswamy; Sudha Thakur; Xiaoyu Chen; Gaurav Kumar; Min Li; Zhijun Yang (MDPI AG, 2021)
Peptides are strings of approximately 2-50 amino acids, which have gained huge attention for theranostic applications in cancer research due to their various advantages including better biosafety, customizability, convenient process of synthesis, targeting ability via recognizing biological receptors on cancer cells, and better ability to penetrate cell membranes. The conjugation of peptides to the various nano delivery systems (NDS) has been found to provide an added benefit toward targeted delivery for cancer therapy. Moreover, the simultaneous delivery of peptide-conjugated NDS and nano probes has shown potential for the diagnosis of the malignant progression of cancer. In this review, various barriers hindering the targeting capacity of NDS are addressed, and various approaches for conjugating peptides and NDS have been discussed. Moreover, major peptide-based functionalized NDS targeting cancer-specific receptors have been considered, including the conjugation of peptides with extracellular vesicles, which are biological nanovesicles with promising ability for therapy and the diagnosis of cancer.